Estimasi Kebutuhan Peralatan Tambang Batubara Untuk Mencapai Target Produksi Pada Tahun 2017 Pt. Partner Resource Indonesia Jobsite Sungai Lilin, Provinsi Sumatera Selatan - Yonal Ferdian; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2018)
Pit yudistira which has value of stripping ratio 1:5.6 is still economical enough to be mined. Considering that of coal is expensive enough this year.To achieve the production target in 2017 of Partner Resource Indonesia company amount 4.020.000bcm overburden it is needed Dig load equipment amount 3 unit of excavator and amount 11 unit of, and amount 708.000 ton of coal it is needed Dig load dumptruck equipment amount 2 unit excavator and 5 unit dumptruck.The level of achievement of production target in 2017 from mechanical equipment which is working to strip the overburden amount 99,32% for excavator and 104,6% for dumptruck with the deficiency of production amount 27416,5 bcm, for demolition of coal amount 103,77% for excavator and 98,34% for dumptruck with the deficiency of production amount 11757,6 ton.To fullfil the deficiency of production target overburden amount 27416,5 bcm in 2017, it should have to added 1 unit of excavator PC by working hours during 288,11 hours. For the amount 111757,6 ton, so it should be added 2 units dumptruck Hino FM 260 by working hours during 201,5 hours. Keywords: Coal’s mine, overburden, production target, dump truck, excavator.